Aspectos jurídicos do coworking - Fischer, Leo Benjamin (2023)
The development of professional activities in coworking spaces is a phenomenon of vertiginous growth both in Brazil and the rest of the world. This new social and economic reality has drawn until now little attention from legal scholars despite the natural and growing doubts of a legal nature that surround these spaces. Moreover, courts have, alternately, designated coworking contracts as typical lease (or sublease) or service agreements or, even, less frequently, as atypical mixed agreements. This academic void and unsettled jurisprudence is the driving motivation behind this paper, which hypothesis is that the coworking agreement is a complex atypical mixed “twin” agreement that merges, in an inextricable manner, multiple provisions of other contracts, thus forming a new specie which has remarkable similarities with the likewise atypical lodging contract, notwithstanding the fact that their objects are different. In order to corroborate this hypothesis, after addressing the genesis, evolution and prospects of the market, we offer our definition of the coworking agreement, break down its main components and identify its legal nature and elements. Thereafter, we contrast the coworking agreement with the lease (and sublease), services and lodging agreements in light of the similarities among the former and the latter, discuss the atypical contract and conclude that the coworking agreement belongs to this designation. Our aim is to thus contribute to fill the scholarly void and to the drafting of the probable future law(s) (coworking is already the object of bills in the federal sphere), as well as to the appeasement of the jurisprudence, regarding which we hint at the correctness of the current minority position. Moreover, we point out the natural legal uncertainties and distortions that this state of scarcity of scholarly papers, lack of regulations and conflicting case law give rise to upon the application of the Law to coworking agreements, including in the consumer, civil and tax liability and condominium spheres